Eccentric Muscle Actions Add Complexity to an Already Inconsistent Resistance Exercise Nomenclature - James L. Nuzzo; Kazunori Nosaka (Sports Medicine - Open, 2023)
Abstract An eccentric muscle action (or contraction) is defined as active muscle lengthening against resistance, which occurs when the force generated by the muscle is smaller than the resistance placed upon it. Eccentric resistance exercise, which involves multiple sessions of repeated eccentric muscle actions, improves muscle strength and other health outcomes. In response to this evidence, new exercise technologies have been developed to permit feasible completion of eccentric muscle actions outside of the laboratory. Consequently, participation in eccentric resistance exercise is projected to increase in the future, and communications about eccentric resistance exercise are likely to reach a wide audience, including students in the classroom, athletes in the weightroom, patients who receive telehealth services,  and journalists who report on study findings. Previous research has documented inconsistencies in how resistance exercises are named, but the role of eccentric resistance exercises has not been considered. Here, we explain how eccentric resistance exercises add further complexity to an already inconsistent resistance exercise nomenclature. Specifically, action words in exercise names typically describe the movement that occurs in the concentric phase (e.g., “press”, “raise”, “curl”, “pull”, “row”). This naming bias likely stems from the fact that traditional resistance exercise equipment, such as free weights and weight stack machines, does not typically accommodate for greater eccentric than concentric strength and thus emphasizes the concentric over eccentric phase. This naming bias is likely to hinder communications about eccentric resistance exercise. Thus, we encourage researchers and practitioners to discuss ways in which resistance exercises can be named more clearly and consistently.